Move analysis in the introduction chapter of thesis written by native English speakers and non-native English speakers - Dan, Chen; Darmi, Ramiza; MD Yusof, Mohamad Ateff (Sciedu Press, 2025)
Genre analysis is essential for understanding rhetorical strategies and enhancing communication for academic purposes. However, constructing effective introduction chapter of PhD (ICPhD) thesis remains challenging due to the diverse rhetorical moves influenced by cultural and linguistic backgrounds. This study employs a corpus-based approach to quantitatively and qualitatively analyze the rhetorical moves in 40 ICPhD theses from top universities in Australia and Malaysia submitted between 2017 to 2022 using Bunton‟s (2002) rhetorical move model. The results reveal significant differences between the two corpora in terms of move frequency, sequence, and cyclicity, as well as the emergence of a new rhetorical move shared by both corpora, especially in Malaysian ICPhD theses. Additionally, the study compares these findings with past research on Australian ICPhD theses (Pawase, 2018), adopting both synchronic and diachronic perspectives to explore the unique challenges posed by language, culture, and educational norms to PhD thesis writers.